Fragile X mental retardation protein regulates translation by binding directly to the ribosome. - Chen, E.; Sharma, M.R.; Shi, X.; Agrawal, R.K.; Joseph, S. (Molecular Cell, 2014)
Fragile X syndrome (FXS) is the most common form of inherited mental retardation, and it is caused by loss of function of the fragile X mental retardation protein (FMRP). FMRP is an RNA-binding protein that is involved in the translational regulation of several neuronal mRNAs. However, the precise mechanism of translational inhibition by FMRP is unknown. Here, we show that FMRP inhibits translation by binding directly to the L5 protein on the 80S ribosome. Furthermore, cryoelectron microscopic reconstruction of the 80S ribosome?FMRP complex shows that FMRP binds within the intersubunit space of the ribosome such that it would preclude the binding of tRNA and translation elongation factors on the ribosome. These findings suggest that FMRP inhibits translation by blocking the essential components of the translational machinery from binding to the ribosome.